2014
DOI: 10.1097/jac.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Health Information Technology Innovation to Improve Quality of Life for Health Plan Members in Urban Safety Net

Abstract: Safety net systems need innovative diabetes self-management programs for linguistically diverse patients. A low-income government-sponsored managed care plan implemented a 27-week automated telephone self-management support (ATSM) / health coaching intervention for English, Spanish-, and Cantonese-speaking members from four publicly-funded clinics in a practice-based research network. Compared to waitlist, immediate intervention participants had greater 6-month improvements in overall diabetes self-care behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…The first limitation, as mentioned, is that the study likely was underpowered for economic outcomes, as the sample size was generated to detect differences in patient-centered outcomes, not economic outcomes. 16 In their previous costeffectiveness analysis involving a prior version of ATSM, 26 the investigators were able to focus on a range of values that met the threshold for cost-effectiveness. However, the current study did not evaluate cost-effectiveness, but differential costs and utilization.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The first limitation, as mentioned, is that the study likely was underpowered for economic outcomes, as the sample size was generated to detect differences in patient-centered outcomes, not economic outcomes. 16 In their previous costeffectiveness analysis involving a prior version of ATSM, 26 the investigators were able to focus on a range of values that met the threshold for cost-effectiveness. However, the current study did not evaluate cost-effectiveness, but differential costs and utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Because the investigators' prior research revealed similar benefits for SMARTSteps-ONLY and SMARTSteps-PLUS participants, 16 for the current analysis these groups were combined and compared to the combined wait-listed groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations